Penerapan Sistem Akuntansi Dengan Basis Teknologi Informasi Sebagai Penunjang Kinerja Karyawan Pada Bank BPR Ekadharma Bhinaraharja Kabupaten Magetan - Siswohadi; Nuryadi; Abdul Manan; Nofia Diah Ayu Tristanti; Jeni Ayu Tria Praneta; Ernawati (CV. Multi Kreasi Media, 2022)
This Community Service aims to describe the development of information technology in the field of accounting has a significant impact, especially on accounting information systems in a business organization. In the world of banking, service is important because performance is directly related to the number of customers. The use of methods in the process of implementing this PKM activity is categorized into five main stages, namely: 1) preparation and organization; 2) preparing the agenda, materials, and training instruments; 3) implementation of training activities; 4) assistance in applying information technology basics; and 5) evaluation. Developments in processing accounting information ultimately have an impact on individual performance and the services provided by banks. So that the achievement of this service activity lies in the effectiveness of time and the convenience that can be obtained with a computerized system that is integrated with information technology. This is indicated by a significant increase in employee performance skills in work management at Bank BPR Ekadharma Bhinaraharja Magetan City.